2017
DOI: 10.2134/agronj2017.02.0069
|View full text |Cite
|
Sign up to set email alerts
|

Five‐Year Forage Dynamics Arising from Four Legume–Grass Seed Mixes

Abstract: Core Ideas Mixtures of legumes and grasses were dynamic in composition over time. Forage mixtures with more legume had less biomass but had stable protein yield. Alfalfa persisted better than clover, and was favored when grown with bunchgrasses. When grown with meadow brome, alfalfa biomass in mixtures was 18 to 42% after 5 yr. Species identity regulated forage productivity more than the proportion legume seeded. To evaluate the comparative role of different legume–grass mixtures on long‐term forage yield, alf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 41 publications
2
10
0
Order By: Relevance
“…While the production environment (year) is a critical factor in forage growth and productivity, the short duration of this study makes it difficult to truly gauge the impact of year on herbage accumulation of the different forage systems. In supporting evidence of our view, Bork et al [50] reported that the maximum yield of grass-legume mixtures was obtained two to three years after seeding. Therefore, our discussion revolves more greatly around the differences in forage accumulation, tissue P concentration, and P removal among forage systems tested.…”
Section: Herbage Accumulationsupporting
confidence: 86%
See 1 more Smart Citation
“…While the production environment (year) is a critical factor in forage growth and productivity, the short duration of this study makes it difficult to truly gauge the impact of year on herbage accumulation of the different forage systems. In supporting evidence of our view, Bork et al [50] reported that the maximum yield of grass-legume mixtures was obtained two to three years after seeding. Therefore, our discussion revolves more greatly around the differences in forage accumulation, tissue P concentration, and P removal among forage systems tested.…”
Section: Herbage Accumulationsupporting
confidence: 86%
“…Hence, we surmised that the legumes had a faster rate of establishment and stability in this study environment compared to the grass monocultures and the grass-legume mixtures similar to the observation made by Aponte et al [37]. However, contrary to our assumption of the legumes in this study, Bork et al [50] reported that legumes (alfalfa and clover) were slow to reach maximum biomass production relative to the grasses. While the production environment (year) is a critical factor in forage growth and productivity, the short duration of this study makes it difficult to truly gauge the impact of year on herbage accumulation of the different forage systems.…”
Section: Herbage Accumulationsupporting
confidence: 84%
“…Our interest to develop legume or legume–grass pasture is motivated by several benefits associated with legume‐based pasture. Studies have indicated higher economic returns on polycultures including perennial legumes over grass monocultures because of their ability to persist longer at a peak dry matter (DM) production level (Bork, Gabruck, McLeod, & Hall, 2017; Ludemann, Jacobs, & Smith, 2015; Malcolm, Smith, & Jacobs, 2014). Cattle also showed preference to legumes over grasses (Boland et al., 2011; Rutter, 2006), and average daily gain (ADG) of cattle on legume‐based pasture was found to be greater than on pure grass pasture (Villalba, Cabassu, & Gunter, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Cattle also showed preference to legumes over grasses (Boland et al., 2011; Rutter, 2006), and average daily gain (ADG) of cattle on legume‐based pasture was found to be greater than on pure grass pasture (Villalba, Cabassu, & Gunter, 2015). Forage mass, nutritive value, and crude protein (CP) concentration of legume alone or legume–grass mixtures was greater than grass monocultures or grass mixtures (Adjesiwor, Islam, Zheljazkov, Ritten, & Garcia y Garcia, 2017; Bork et al., 2017; Brink, Casler, & Hall, 2007; Brink, Sanderson, & Casler, 2015; Picasso, Brummer, Liebman, Dixon, & Wilsey, 2008; Schmid, Hector, Saha, & Loreau, 2008; Sleugh, Moore, George, & Brummer, 2000). Despite the higher seasonal biomass yield distribution of binary mixture of legume and grass over grass or legume monocultures (Sleugh et al., 2000, Sturludóttir et al., 2014), herbage digestibility was not compromised (Sturludóttir et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It also mixes well with grasses such as tall fescue (Lolium arundinaceum (Schreb.) Darbyshand) and orchardgrass (Dactylis glomerata L.) (Robins and Jensen, 2017;Bork et al, 2017).…”
mentioning
confidence: 99%